Assessment of Utilization of Primary Health Care Services and Quality Health System Among Inhabitants of Wukari Local Government, Taraba State, Nigeria - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Usman Ikrimah; Nehemiah, Timothy; Onyemaechi, Eze Emmanuel; Ladan, Shuaibu Adamu; Rita, Odey Catharine (Darul Yasin Al Sys, 2025)
This study assesses the utilization of Primary Health Care (PHC) services and the perceived quality of the healthcare system among residents of Wukari Local Government Area, Taraba State, Nigeria. While the presence of health facilities is crucial, access and utilization are influenced by a range of socioeconomic factors. Using a cross-sectional survey design, the demographic analysis revealed that the majority of respondents (59%) were aged 20–39 years, with 58% female and 42% male participants. Educational levels varied, with 37% having secondary education, 27% primary education, 20% no formal education, and 16% tertiary education. Marital status data showed 52% were single, 32% married, and 16% divorced, while religious affiliation indicated that 54% were Christians, 32% practiced African traditional religions, and 14% were Muslims. Occupationally, 53% were farmers, 26% civil/public servants, 13% artisans, and 7% petty traders. Findings revealed that major barriers to PHC utilization included inadequate staffing (90%), high drug costs (95%), long waiting times (80%), poor staff attitudes (85%), and long distances to health facilities (70%). Notably, 75% of respondents did not consider staff incompetence a major issue. Regarding satisfaction, high levels of dissatisfaction were recorded with service charges (75%), drug supply (90%), treatment modalities (60%), chronic disease management (95%), child care services (87.5%), antenatal care (90%), and delivery services (87.5%). Chi-square analysis showed a statistically significant relationship between PHC facility-related factors and service utilization (χ² = 250.7, df = 18, p < 0.001). The study concludes that despite the availability of PHC facilities, critical issues such as cost, accessibility, quality of care, and staff performance hinder effective utilization. It recommends targeted policy interventions to improve staffing, service delivery, affordability, and access to ensure equitable and efficient primary healthcare in Wukari.